Установка для экспресс-контроля глубины охлаждения термоэлектрических микромодулей Пельтье - Ascheulov, А. А.; Velichuk, D. D.; Romanyuk, I. S. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
A setup has been designed for rapid control of cooling depth, cooling capacity, optimal current, and power consumption of thermoelectric Peltier coolers. Its application enables investigation of both static and dynamic characteristics of thermoelectric coolers across a wide temperature range.